2020
DOI: 10.1097/md.0000000000020927
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative serum albumin, albumin-to-globulin ratio, and prognostic nutritional index for patients with glioma

Abstract: Background: The serum albumin, albumin-to-globulin ratio (AGR), and prognostic nutritional index (PNI) have been recommended to represent the nutritional and inflammatory status. Thus, they may be potential prognostic biomarkers for cancer. However, contradictory results were reported in different studies on glioma. The goal of this study was to perform a meta-analysis to re-evaluate their prognostic potential for glioma. Methods: Databases of PubMed, EMBASE, and Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…In the meta-analysis of Liu and Wang, subgroup analysis indicate that albumin is a significant prognostic indicator for GBM patients (HR=0.95, 95% CI: 0.91–0.99, p=0.018), especially in multivariate analysis. 38 …”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis of Liu and Wang, subgroup analysis indicate that albumin is a significant prognostic indicator for GBM patients (HR=0.95, 95% CI: 0.91–0.99, p=0.018), especially in multivariate analysis. 38 …”
Section: Discussionmentioning
confidence: 99%
“…In 2020, a systematic review and meta-analysis investigated the prognostic value of albumin, albumin-to-globulin ratio (AGR), and PNI for glioma (47). In this review, 9 of the 11 included studies investigated the association between PNI and OS in patients with glioma.…”
Section: Central Nervous System Tumorsmentioning
confidence: 99%
“…More and more studies found that higher PNI can be used for independent factors for better prognosis of various malignant tumors, such as lung cancer (6), esophageal cancer (7), breast cancer (8), nasopharyngeal cancer (9), colorectal cancer (10), gastric cancer (11), and biliary tract cancer (12). However, there is no consensus on the role of PNI in glioma (13). Therefore, this study intended to explore the prognostic value of PNI in patients with operable highgrade glioma.…”
Section: Introductionmentioning
confidence: 99%